Nuclear Energy's Environmental Imperatives A Global Perspective - Nishonov , Abdulloh Ubaydulloh o’g’li (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the requirements and prospects of utilizing nuclear energy amid the global energy crisis, focusing on environmental considerations, regulatory frameworks, and sustainable deployment strategies. Drawing on multidisciplinary approaches and insights from renowned scientists, it examines the environmental impact assessment measures, international agreements, and development prospects associated with nuclear energy. The findings underscore the importance of stringent environmental standards and sustainable deployment strategies for ensuring the viability of nuclear energy as a crucial component of the global energy mix, offering valuable insights for policymakers and stakeholders in the energy sector. Highlights: Comprehensive analysis of nuclear energy's environmental requirements. Examination of international agreements regulating atomic energy. Importance of sustainable deployment strategies amidst the global energy crisis. Keywords: Atom Energy, Radiation Problems, Disaster, Harmful Emissions